Answer:
h'(1)=0
Explanation:
We use the definition of the derivative of a quotient:
If
, then:
![h'(x)=(f'(x)*g(x)-f(x)*g'(x))/((g(x))^2)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/bdexi8rcwzle5dutbrpwepa7lwiuxf7c12.png)
Since in our case we want the derivative of
at the point x = 1, which is indicated by: h'(1), we need to evaluate the previous expression at x = 1, that is:
![h'(1)=(f'(1)*g(1)-f(1)*g'(1))/((g(1))^2)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/3tbuzirykzr484suoqcn6fbs93g9nfy2ce.png)
which, by replacing with the given numerical values:
![f(1) =4\\g(1)=3\\f'(1)=-4\\g'(1)=-3](https://img.qammunity.org/2020/formulas/mathematics/middle-school/xc6vani94mj1laszg17fwa4bttu6uahl7g.png)
becomes:
![h'(1)=(f'(1)*g(1)-f(1)*g'(1))/((g(1))^2)=\\=(-4*3-4*(-3))/((3)^2)=(-12+12)/(9) =(0)/(9) =0](https://img.qammunity.org/2020/formulas/mathematics/middle-school/y4smhvw6ouymm1rdzsiuv5017etr6fql43.png)